Karakteristik Fisikokimia dan Organoleptik Pepes Daging Itik Petelur Afkir yang Dilumuri Bubuk Daun Nangka (Artocarpus heterophyllus) - Pratiwi, Oklivia Nesia; Suharyanto, Suharyanto; Warnoto, Warnoto (Buletin Peternakan Tropis, 2021)
This study aimed to analyze the physicochemical and organoleptic characteristics of rejected laying duck meat pepes after being coated with jackfruit leaf powder (JLP). The research design employed was a completely randomized design consisting of 4 treatments (P0: without any coating with JLP; P1: 5%; P2: 10%; and P3: 15% smearing of JLP) with 3 replications. The variables measured were cooking loss, water holding capacity (WHC), pH, and water content which were analyzed by Anova and multiple comparisons DMRT by significance level 0.05, and organoleptic which were analyzed by description. The results of the study showed that rejected laying duck meat smeared with JLP had no significant effect (P>0.05) on cooking loss, WHC pH, and moisture content of the pepes. However, the 15% JLP was able to enhance the aroma of the pepes. The average range value of the cooking loss was 14.00 to 15.33%, the WHC was 53.76-55.47%, the pH value was 6.22-6.29%, and the moisture content was 67.83-71,28%. The results of the hedonic quality test showed that the average value of the meat aroma ranged from 4.03-4.20 in the slightly fishy to a very non-fishy category, the interval scale test results showed P0, P1, and P2 in an interval scale of 3.40-4.19 (slightly fishy aroma), different from P3 which is included in the interval scale from 4.20 to 5.00 (very not fishy). The tenderness of the meat was 3.52-3.92 as the tender category, the taste of the meat was 3.88-4.10 as the delicious category. The results of the hedonic test showed that the average value of the aroma of meat ranged from 4.02-4.12, the tenderness from 3.39-3.64, and the taste from 3.88-3.97. All scores were in the liking category. It was concluded that 5% to 15% smearing of JLP did not change the physicochemical properties of rejected layer duck meat paste, but 15% application of it could increase the aroma.